2019
DOI: 10.1921/swssr.v20i2.1246
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Student-Athletes using Protective Behavioral Strategies and Alcohol Use Based on Cluster Analysis Assignment

Abstract: An estimated 2 in 3 college students report consuming alcohol in the past month and 44% of students report engaging in high risk or heavy episodic drinking at least once in the previous 2 weeks. Despite evidence suggesting that participation in sports may be a protective factor for the use of alcohol, recent data from the National Collegiate Athletic Association (NCAA), finds that 77% college student-athletes report use. Though overall prevalence rates of alcohol consumption are similar among college student-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Not all research works have revealed an association between sport participation and the positive development of the participants. In this regard, a study of the Healthy Sport Index determined that high school athletes, in comparison to non-athletes are more prone to indulge in consuming alcohol with children participating in a sport like wrestling, football and lacrosse and exhibiting the most dangerous offfield conduct (Sanders, Dudley, Milroy & Wyrick, 2018). Another research study indicated that there were adverse effects of sports participation on students' test scores (Kramer et al, 2019).…”
Section: Correlation Analysis (Association)mentioning
confidence: 99%
“…Not all research works have revealed an association between sport participation and the positive development of the participants. In this regard, a study of the Healthy Sport Index determined that high school athletes, in comparison to non-athletes are more prone to indulge in consuming alcohol with children participating in a sport like wrestling, football and lacrosse and exhibiting the most dangerous offfield conduct (Sanders, Dudley, Milroy & Wyrick, 2018). Another research study indicated that there were adverse effects of sports participation on students' test scores (Kramer et al, 2019).…”
Section: Correlation Analysis (Association)mentioning
confidence: 99%